Fast in situ 3D nanoimaging: a new tool for dynamic characterization in materials science. Issue 7 (September 2017) - Villanova, Julie; Daudin, Rémi; Lhuissier, Pierre; Jauffrès, David; Lou, Siyu; Martin, Christophe L.; Labouré, Sylvain; Tucoulou, Rémi; Martínez-Criado, Gema; Salvo, Luc
Graphical abstract: Abstract : The performance of many advanced materials is determined by the arrangement of their nanostructure which requires ever more precise characterization. In this respect, X-ray computed tomography (CT) is a powerful technique to investigate material properties as it provides non-destructive direct access to three-dimensional morphology with nanoscale resolution. However, challenges remain in clearly understanding physical mechanisms involved during their processing in real time and real conditions. So far, beam and sample stabilities, effective spatial resolution and tomography scan time have hindered the development of nanoscale in situ 4D imaging (3D plus time), and especially at high temperatures. Here, we report on the development of fast X-ray nanotomography at temperatures up to 700°C with an unprecedented combination of nanometer pixel size and acquisition times of a few tens of seconds. The great potential of the method is demonstrated by following the early stages of two thermally driven phenomena: neck curvature evolution in sintering and nucleation of liquid droplets in light alloys. The reported real time observations will benefit the fundamental understanding of the underlying physics and provide useful data to build new models. The novel aspects of this synchrotron based technique offer a powerful imaging tool for a wide variety of heterogeneous nanoscale dynamics in materials and open new perspectives for the investigation of advanced materials under realistic conditions.